UBS 02 de Brazlândia: uma proposta de intervenção no acesso dos usuários - Reis, Aline Fernanda de Sá; Sousa, Eliene Ferreira de; Kubitschek, Fernanda da Cruz; Dias, Jean Ponciano do Nascimento; Mourão, Kely Rodrigues; Nery, Márcia Costa Pinheiro; Ribeiro, Perla Estrela; Araújo, Silvana Reigota Naves de; Tatiana Fonseca Rocha Vicente; Ferreira, Walkíria Warley; Moro, Maria Francisca Santos Abritta; Almeida, Karlo Josefo Quadros de (Revista Acadêmica GUETO, 2024)
Projeto